Customer Interest Orientation in Islamic Banks: A Bibliometric Analysis of Islamic Banking Research in Indonesia - Nur Wafiq Azizah; Fauzi Arif Lubis; Nur Ahmadi Bi Rahmani (Seutia Hukamaa Cendekia, 2026)
This study maps the development of scientific research on customer interest in Islamic banking through a bibliometric analysis. The method is quantitative and descriptive, using Publish or Perish to collect data from Google Scholar and VOSviewer to analyse it. Research data were obtained from the Google Scholar database using the keyword “customer interest in Islamic banks” and a publication date range of 2015–2025, with a maximum of 500 articles. Bibliographic data were then processed in Microsoft Excel and visualised in VOSviewer to identify patterns of relationships between keywords, research trends, and emerging topic clusters. The results show that research on Islamic bank customers' interest has developed alongside increasing attention to factors such as religiosity, service quality, Islamic financial literacy, digital innovation, and trust in Islamic financial institutions. In addition, bibliometric visualisation reveals several clusters of research themes that illustrate the relationships among customer behaviour, digital technology, and Sharia principles. This study provides an overview of the development of academic research on customers' interest in Islamic banks and identifies opportunities for further research in Islamic banking in Indonesia.